Brine shrimp lethality bioassay of Eleutherine Bulbosa (Miller) urban - RANI.V.S, (International Journal of Pharma and Bio Sciences, 2018)
The present study deals with the cytotoxic property of various extracts of of Eleutherine bulbosa bulbs.It was evaluated by a simple, low cost bioassay such as brine shrimp lethality assay. It was found that the crude ethyl acetate extract of the plant exhibited significant toxicity against the shrimp larvae (nauplii) when compared to that of potassium permanganate (positive control) and it is a good indicator of toxicity. The results suggested that crude ethyl acetate extract of E.bulbosa bulb possesses significant cytotoxic activity. The LC50 value of crude ethyl acetate extract at 95% confidence limit is 6.276μg/ml – 8.073μg/ml. A proper chemical profiling of this extract is therefore warranted in order to find out the specific compound responsible for the bioactivity.